Distribution Characteristics of Organochlorine Pesticides in Soil and Groundwater of Different Irrigation Areas in Southeast Suburb of Beijing - Jiang-tao, He; Wen-jie, Ma; Ai-Fang, Jin; Yong-Xia, Wei (IntechOpen, 2011)
None